Improving Young Athletes' Life Skills Through An Integrated Early Age Football Competition Model In The Framework Of Positive Youth Development - Hulfian, Lalu; Hermasnyah, Hermansyah; Triansyah, Andika; Agus, Herdiansyah (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
The background of this research is based on the importance of developing young athletes, emphasizing not only technical sports skills but also character development, social skills, and readiness to face life's challenges. This study aims to analyze the effectiveness of an integrated competition model in improving the life skills of young athletes as part of Positive Youth Development (PYD) efforts. The research method used was a quasi-experimental design with a pretest-posttest control group. The research subjects consisted of young athletes aged 12–16 years with a total sample of 48 athletes (24 experimental; 24 control). The average -pretest score of the experimental group was 142.8 ± 9.4 and increased in the posttest to 147.1 ± 8.7 (Δ = +4.33). The control group increased from 141.9 ± 9.1 to 142.1 ± 8.5 (Δ = +0.17). The treatment effect showed a significant difference (t = 8.29; p < 0.001) with a Cohen's d effect size of 1.69. The integrated competition model resulted in the largest improvements in teamwork (20%) and communication (18%). These findings confirm that combining competitive elements with life skills learning structures is an effective strategy in supporting Positive Youth Development. Keywords: life skills, young athletes, integrated competition model, positive youth development